Middle to Late Neolithic animal exploitation at UAQ2 (5500-4000 cal BC): an ʿUbaid-related coastal site at Umm al-Quwain Emirate, United Arab Emirates - Mashkour, Marjan; Beech, Mark Jonathan; Debue, Karyne; Yeomans, Lisa; Bréhard, Stéphanie; Gasparini, Dalia; Méry, Sophie (Proceedings of the Seminar for Arabian Studies, 2016)
The subsistence strategies of coastal Neolithic groups in eastern Arabia, reliant upon the exploitation of marine and terrestrial animal resources, are not yet fully understood. A central question in relevant literature is the issue of mobility. This is the reason for excavations in Umm al-Quwain (UAQ2), UAE, from 2011 by the French Archaeological Mission. UAQ2 is a site with obvious potential, occupied for 1500 years from the mid-sixth millennium BC. It has an area of approximately 6 ha with 3.2 m or more of imposing and unusual stratigraphy. A large quantity of faunal remains, including terrestrial and marine vertebrates, was recovered from UAQ2. The terrestrial mammals are composed mainly of domestic herbivores including caprines, cattle, and dogs. The most striking feature is the number of newly born and young animals among the small herbivores, a clear indication of occupation during late winter/spring. As for the fish bones, the following taxa were identified: requiem sharks, shark-suckers, marine catfish, needlefish, jacks/trevallies, milkfish, mojarra, emperors, snappers, mullet, flatheads, shortfin flounders, parrotfish, kawakawa, tuna, groupers, sea bream, barracuda, puffer, and tripod fish. These indicate that most fishing was carried out in the shallow lagoon area, but some fishing for tuna may have been carried out in the open seas beyond the local lagoon. Besides fish were also the remains of cuttlefish and swimming crabs. This assemblage provides new information on the mixed exploitation of inland and marine resources during the sixth to fifth millennium BC. The integrated study of the faunal remains contributes to the proposal of a possible year-round residency, not excluding coastal mobility.